Facebook for self-empowerment? A study of Facebook adoption in urban India. (November 2014) - Kumar, Neha
This article presents an ethnographic study of the adoption and use of Facebook among urban Indian youth from socioeconomically disadvantaged communities. Mobile-centric use of the Internet is widely prevalent here as general packet radio service (GPRS)-enabled mobile phones and data plans have become increasingly affordable. Less privileged youth are the lead adopters of these new technologies, and typically the first generation of Internet users, in their communities. My research uncovers their leisure-driven engagement with new media, seen through the lens of Facebook use, and the development-friendly outcomes that result from it. By examining the direct and indirect affordances of Facebook perceived by these youth, this article highlights how they swiftly negotiate social boundaries and technological hurdles, transitioning into legitimate members of a global community.